Two-Layer Stackelberg Game Model for Energy Supply and Demand in the Park - Peng LU; Chunxian FENG; Weiming WU; Tieqiang WANG; Lijuan XIE; Rui MA (Zhongguo dianli)
Aiming at the optimization of the price and quantity of energy dealers and users in energy trading in the park, this paper proposef a two-layer Stackelberg game model of the price and quantity of energy supply and demand in the park.The upper-level model energy business aimed to maximize its own interests, considered the multi-energy flow rate balance constraints and external grid interaction constraints, power-to-gas, power/heat, gas turbines and other source-storage constraints, at the same time determined energy prices through competition. The lower model considered the user's energy demand response, aimed to minimize the energy cost, considered the load demand constraint, and determines the energy demand according to the decision price of the energy supplier. The energy supplier further optimized the energy price according to the user's energy demand, and iterated until convergence. The results of the example show that it can effectively maximize the benefits of both parties.